2021
DOI: 10.1007/s10015-021-00709-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of food intake on task engagement based on psychophysiological states

Abstract: The objective of this study was to evaluate the effects of food intake on performance and task engagement based on psychophysiological states. The experiment was conducted under two conditions: taking a break with his eyes opened between the repeated tracking tasks (Control), and taking a break with food intake (Intake). We found the rate of deterioration of the distance between target pointer and the mouse cursor, a performance index, showed significant differences between the two conditions. Significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Five subjective feelings, hemodynamic parameters, and EEGs were measured to assess physiological and psychological states. These biometric experiments were performed using the same systems, procedures, and conditions as those used in a previous study [11]. This study was approved by the Life Science Committee of the Department of Science and Engineering at Aoyama Gakuin University (approval number: M13-17).…”
Section: Biometric Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five subjective feelings, hemodynamic parameters, and EEGs were measured to assess physiological and psychological states. These biometric experiments were performed using the same systems, procedures, and conditions as those used in a previous study [11]. This study was approved by the Life Science Committee of the Department of Science and Engineering at Aoyama Gakuin University (approval number: M13-17).…”
Section: Biometric Experimentsmentioning
confidence: 99%
“…In addition, when the MBP decreased, it was classified as no stress coping. In a previous study [11], stress-coping styles were used to assess differences in task engagement with and without food. The results showed that there was a difference in task engagement between those who ate and those who did not.…”
Section: Indices For Analysismentioning
confidence: 99%